2019
DOI: 10.1152/japplphysiol.00800.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent exacerbation of ventilation-induced lung injury by erythropoietin in preterm newborn lambs

Abstract: Erythropoietin (EPO) is being trialled in preterm infants to reduce brain injury, but high doses increase lung injury in ventilated preterm lambs. We aimed to determine whether early administration of lower doses of EPO could reduce ventilation-induced lung injury and systemic inflammation in preterm lambs. Ventilation was initiated in anaesthetized preterm lambs [125 ± 1 (SD) days gestation] using an injurious strategy for the first 15 min. Lambs were subsequently ventilated with a protective strategy for a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…These findings led in turn to clinical trials (see below). Subsequent studies in preterm lambs suggested that a lower single dose of EPO at 1000 IU/kg may be the optimal dose, compared with 3000 IU/kg and 5000 IU/kg, to achieve both lung and brain protection in preterm infants [139][140][141][142]. The latter results are particularly relevant to ventilated preterm infants, which constitute the majority of these neonates.…”
Section: Effects Of Epo In Clinical Trials For Preterm Infantsmentioning
confidence: 99%
“…These findings led in turn to clinical trials (see below). Subsequent studies in preterm lambs suggested that a lower single dose of EPO at 1000 IU/kg may be the optimal dose, compared with 3000 IU/kg and 5000 IU/kg, to achieve both lung and brain protection in preterm infants [139][140][141][142]. The latter results are particularly relevant to ventilated preterm infants, which constitute the majority of these neonates.…”
Section: Effects Of Epo In Clinical Trials For Preterm Infantsmentioning
confidence: 99%
“…54,55 In addition, recent studies shown that administration of bone marrow MSCs in combination with rEPO, which could suppress EMT process by inhibiting the transforming growth factor-β1 signaling pathway, significantly attenuated hyperoxia-induced lung damage and maybe a promising therapeutic strategy. 53,56,57 However, Polglase et al 58,59 investigated whether a single dose of rEPO administration can protect the lung from ventilation induced injury in preterm lambs. Their findings demonstrated that administration of high-dose rEPO (i.v.…”
Section: Discussionmentioning
confidence: 99%
“…When administered to preterm lambs that received 15 min of injurious high V T ventilation, single early low doses of 300 IU/kg and 1,000 IU/kg human recombinant EPO did not reduce or exacerbate lung and brain injury (124,125), suggesting that EPO doses presently used in clinical trials appear to be safe for preterm infants receiving respiratory support. However, they appear to not be efficacious as a therapy for VIBI given the lack of therapeutic potential observed.…”
Section: Bench To Bedsidementioning
confidence: 92%
“…High doses of EPO of 3,000 IU/kg and 5,000 IU/kg increased cerebrospinal fluid EPO levels to “neuroprotective levels” [>100 mU/ml ( 126 )] within 2 h of administration ( 73 , 124 ). These high doses, respectively, had a protective effect on blood-brain barrier integrity ( 124 ) and differential regional effects on white matter ( 73 ) despite both doses amplifying lung inflammation and injury ( 125 , 127 ). Together, these data highlight a complex dose response with distinct effects on the lungs and brain, indicating that further investigation is required to elucidate the efficacy of EPO in the context of a preterm infant requiring respiratory support.…”
Section: Bench To Bedsidementioning
confidence: 99%